Popova E. V. Сoncatenation of intra- and extralingustic factors - Popova E. V. (Philological Treatises, 2020)
The article deals with the investigation of social factors and cognitive-pragmatic reasoning as a language system development canvas, that may lead occasional constructions to active usage and normative codification.